2017
DOI: 10.1002/jbio.201700124
|View full text |Cite
|
Sign up to set email alerts
|

Current status, pitfalls and future directions in the diagnosis and therapy of lymphatic malformation

Abstract: Lymphatic malformations are complex congenital vascular lesions composed of dilated, abnormal lymphatic channels of varying size that can result in significant esthetic and physical impairment due to relentless growth. Lymphatic malformations comprised of micro-lymphatic channels (microcystic) integrate and infiltrate normal soft tissue, leading to a locally invasive mass. Ultrasonography and magnetic resonance imaging assist in the diagnosis but are unable to detect microvasculature present in microcystic lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 95 publications
0
39
0
Order By: Relevance
“…The etiology of lymphatic malformations is unclear. However, it is certain that lymphatic malformations consist of an accumulation of fluid resulting from an abnormal drainage pattern of lymphatic vessels [8]. In the head and neck region, the incidence rate of this condition is roughly 1 in 2,000 to 4,000 live births, but it is only rarely seen on the upper extremities as a macrocystic lesion [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The etiology of lymphatic malformations is unclear. However, it is certain that lymphatic malformations consist of an accumulation of fluid resulting from an abnormal drainage pattern of lymphatic vessels [8]. In the head and neck region, the incidence rate of this condition is roughly 1 in 2,000 to 4,000 live births, but it is only rarely seen on the upper extremities as a macrocystic lesion [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is certain that lymphatic malformations consist of an accumulation of fluid resulting from an abnormal drainage pattern of lymphatic vessels [8]. In the head and neck region, the incidence rate of this condition is roughly 1 in 2,000 to 4,000 live births, but it is only rarely seen on the upper extremities as a macrocystic lesion [8]. Okazaki et al [9] reported their experiences with 128 cases of lymphatic malformation, none of which were cutaneous cystic lymphatic malformations on the upper extremities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,17 Recent studies from different research groups on immersion OC at application of widely used OCAs to OA/PA systems showed great benefits expressed in much better probing depth and spatial resolution of these systems. 198,285,[286][287][288][289][290][291][292][293] First, it was demonstrated for optical resolution PA microscopy (OR-PAM) in two different modifications. 287,288 As in OR-PAM, the lateral resolution is determined by the diffraction-limited light focusing, which degrades due to light scattering, and the probing depth is limited by the photon transport mean free path, which is also in tissues determined by light scattering, suppression of scattering at tissue interaction with an OCA strongly improves these characteristics of the microscope.…”
Section: Wavefront Shaping and Computational Tissue Optical Clearingmentioning
confidence: 99%